Diagnostic Potential of Open Lung Biopsy in Mechanically Ventilated Patients with Diffuse Pulmonary Infiltrates of Unclear Aetiology. Issue 5 (September 2013) - Depuydt, O. E.; Daeze, C.; Benoit, D.; Praet, M.; Vermassen, E.; Decruyenaere, M.
Acute respiratory failure with bilateral pulmonary infiltrates is a clinical problem with a wide differential diagnosis. We evaluated whether open lung biopsy offered a diagnosis and therapeutic guidance in cases of unclear diagnosis after non-invasive tests. For this purpose, we reviewed 60 cases of open lung biopsy performed between 2002 and 2009 in patients with acute respiratory failure and bilateral infiltrates at the intensive care unit of Ghent University Hospital. Pathological diagnosis was classified as specific or non-specific and its contribution to therapy and decision-making was evaluated by a panel of three intensive care unit physicians. We found that a specific pathological diagnosis was present in 39 open lung biopsy patients (65%; 95% confidence interval 52 to 76%): idiopathic interstitial pneumonia in 24 patients, malignancy in four patients, pulmonary infectious disease in nine patients, and a combination of specific diagnoses in two patients. Open lung biopsy contributed to patient management in 53 cases (88%) as it led to the initiation, modification or discontinuation of therapeutic drugs in 36, and contributed to the decision to continue or withdraw ventilator support in 17. Complications of open lung biopsy were noted in 14 patients (23%). We conclude that open lung biopsy was a useful diagnostic intervention in of a selected group of patients with acute respiratory failure and bilateral infiltrates of unclear clinical diagnosis, as it offered a specific diagnosis in 65%.